Clinical features and prognostic factors of COVID-19 in people living with HIV hospitalized with suspected or confirmed SARS-CoV-2 infection : 15 July 2021 (World Health Organization, 2021)
This report describes the demographics, clinical presentation, clinical outcomes, and risk factors among people living with HIV (PLHIV) who have been hospitalized for suspected or confirmed COVID-19.
Keywords: rizikové faktory; Betacoronavirus; hospitalizace; mortalita; prognóza; Prognosis; Risk Factors; veřejné zdravotnictví; epidemický výskyt choroby; infekční lékařství; Disease Outbreaks; Mortality; Meta-Analysis as Topic; Hospitalization; metaanalýza jako téma; COVID-19; HIV